2006
DOI: 10.1007/s11894-006-0051-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and irritable bowel syndrome: The evidence for small intestinal bacterial overgrowth

Abstract: Irritable bowel syndrome (IBS) is a complex, yet common diagnosis in gastroenterology. Recent data suggest the increasing importance of bacteria in the pathophysiology of IBS. Some studies have shown that IBS can be precipitated by an acute case of gastroenteritis. These pathogenic organisms may contribute to long-term gut dysfunction. In another line of effort, a growing body of evidence links IBS to the presence of excessive bacteria in the small bowel, called bacterial overgrowth. Although the means by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…This definition was based on (a) former publications about the definition of SIBO [11], and (b) on a preliminary cohort of 15 patients undergoing upper GI tract endoscopy for mild dyspepsia. These patients had negative histories for co-morbidities and for drug intake and they did not have any finding on endoscopy.…”
Section: Laboratory Investigationmentioning
confidence: 99%
“…This definition was based on (a) former publications about the definition of SIBO [11], and (b) on a preliminary cohort of 15 patients undergoing upper GI tract endoscopy for mild dyspepsia. These patients had negative histories for co-morbidities and for drug intake and they did not have any finding on endoscopy.…”
Section: Laboratory Investigationmentioning
confidence: 99%
“…These pathogenic organisms may contribute to long-term gut dysfunction. In another line of effort, a growing body of evidence links IBS to the presence of excessive bacteria in the small bowel, called bacterial overgrowth [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some IBS patients appear to have abnormal lactulose breath tests, implicating bacterial overgrowth as contributing to the pathogenesis of IBS [37]. A link between IBS and bacterial overgrowth is further supported by an up to 75% improvement in gastrointestinal complaints after neomycin treatment [37]. Similar improvement has been noted after treatment with rifaximin.…”
Section: Irritable Bowel Syndromementioning
confidence: 90%
“…A recent study has demonstrated decreased levels of coliforms, lactobacilli, and bifidobacteria in the feces of IBS patients and increased anaerobes, including Bacteroides spp, in the colonic mucosa [36]. Furthermore, some IBS patients appear to have abnormal lactulose breath tests, implicating bacterial overgrowth as contributing to the pathogenesis of IBS [37]. A link between IBS and bacterial overgrowth is further supported by an up to 75% improvement in gastrointestinal complaints after neomycin treatment [37].…”
Section: Irritable Bowel Syndromementioning
confidence: 99%